Application of recirculation technology to improve Tilapia breeding productivity in tarpaulin ponds - Pahmi Ansyari; Slamat Slamat; Noor Arida Fauzana; Irma Febrianty (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
Tilapia farming continues to grow and requires seeds that are very large in number and superior in quality. This community service activity is the application of tilapia hatchery technology with a recirculation system in tarpaulin ponds, which is a modern technology, capital-intensive, but highly productive. The strategic intermediate target audience is the members of the Badan Pengembangan Usaha Pasantren (BPUP) Nurul Muhibbin, Halong, Balangan Regency, South Kalimantan. The method of delivering technology dissemination is a theoretical explanation with lecture and FGD methods, then demonstration and mentoring. The results of the activity from the parameters of egg hatchability with recirculation 57,6 percent and survival 49,3 percent higher than without recirculation, and the production of tilapia seed size 1 - 3 cm, 156,000 fish during 4 months of activity, and these results show high productivity. The profit obtained for 4 months was Rp 15,400,000.00 B/C ratio = 1.89 and RPI = 3.13, which means it is very feasible to be cultivated. Furthermore, the results of the mean equality test of the pre-test and post-test target audiences showed a significant increase 96 percent in knowledge and skills, compared to before the activity, only 67 percent.